The Biochemistry of Malic Acid Metabolism by Wine Yeasts – A Review - Saayman, M.; Viljoen-Bloom, M. (South African Journal of Enology and Viticulture, 2017)
L-Malic acid is an essential intermediate of cell metabolism and the D,L-racemic mixture is used as an acidulant in a variety of foods and beverages. In the wine industry, it plays an important role during grape must fermentation, contributing to the “fixed acidity” that is important. The latter is important in defining the quality of wine. Genetic and biochemical characterisation of the L-malate utilising pathways in several yeast species has indicated that the physiological role and regulation of L-malate metabolism differ significantly between the K(-) and K(+) yeasts. A variety of factors influence the ability of a yeast species to effectively degrade L-malate, including the conditions associated with wine fermentation and the yeast’s intrinsic ability to transport and effectively metabolise L-malate inside the cell. This paper reviews the ability of different yeast species associated with grapes and wine to degrade extracellular L-malate, and the underlying mechanisms in the differential utilisation of L-malate by different yeast species.